Place and space for women in a rural area in Iceland - Anna Guðrún (Gudrun) (University of Aberdeen, School of Education, 2013)
The aim of this article is to explore what happens when women in Iceland try to reinhabit their 'place' in the community by undertaking university studies through distance learning. The research builds on interviews with eight women from the remote Westfjords area in Iceland. They had all taken a higher educational degree through distance learning while living in their hometown, and were still living there on completion of their studies. My argument is that women use education to strengthen their status, place and space in a rural community. The findings show however, that because their study is mostly in the field of the private sphere of life, they only strengthen their status inside that field, not extending their action space within the community. On the surface it looks as if they are studying for themselves, but under the surface, it becomes clear that the area they choose to study fits the needs of the community; that is, a profession that is lacking.